Desenvolvimento de propostas metodológicas para o trabalho interdisciplinar nas disciplinas de matemática e física - Kleemann, Robson (2018)
The present work evidences the importance of the use of interdisciplinarity and the use of technological resources in the pedagogical practice, presenting three methodological proposals for the teaching of Mathematics from interdisciplinary relations with problems of the discipline of Physics, having GeoGebra software as intermediary support. Addressed the topics involving spherical mirrors and the similarity of triangles: characterization of the images from the position of the object in relation to the mirror; waves, satellite signals and the parabola: functioning of a satellite dish; and Kepler's Laws and the Ellipse: the locus of the trajectory described by the planets around the Sun. In addition, is available, online, a pedagogical material on the subject of methodological proposals, developed from GeoGebra.